KONSEP TOLERANSI MENURUT QURAISH SHIHAB PADA SURAH AL-KAFIRUN - Setio Budi, Setio Budi (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2022)
This paper describes the boundaries of religion in Islam, especially the problem of tolerance. This is based on the fact that many Muslims do not know how far the limits of tolerance are allowed in Islam. Therefore, this study aims to find the concept of religion according to the instructions of the Qur'an in Surah al-Kafirun. Using the library research method using library data, the results of the study show that the concept of tolerance offered in Surat al-Kafirun is only limited to acceptance, tolerance and respect for the views of other parties, without having to sacrifice religion. Meanwhile, the meaning of tolerance in Surah al-Kafirun according to Quraish Shihab is more about the meaning of compromise.